First Line Treatment for Metastatic Pancreatic Adenocarcinoma: Looking for the Step Forward - Ramfidis, Vasilis S; Psyrri, Amanda; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is a lethal disease and its prognosis remains dismal. The modest results of existing available treatments in the first line setting reveal the need of new therapeutic strategies. In this year’s American Society of Clinical Oncology (ASCO) Annual Meeting four remarkable studies were presented regarding this vulnerable group of patients. The efficacy and toxicity profile of gemcitabine plus erlotinib plus capecitabine (Abstract #4122), refametinib plus gemcitabine (Abstract #4025), gemcitabine plus docetaxel plus capecitabine plus cisplatin (Abstract #4135) were examined and the predictive value of a biomarker panel testing response to gemcitabine with or without the addition of erlotinib (Abstract #4133) was also presented. Image: Therapeutic strategies in first line setting of advanced or metastatic pancreatic adenocarcinoma